Radical SAM cyclophane synthase catalyzes uniform cyclophane formation at multiple Trp-motifs - Abujunaid Habib Khan; Jabal Rahmat Haedar; Anitra Zīle; Chin-Soon Phan (Tetrahedron Chem)
Cyclophane-containing products from ribosomally synthesized and post-translationally modified peptides (RiPPs) are generated by radical SAM cyclophane synthases (rSAM). In the past few years, rSAM enzymes that catalyze uniform cyclophanes at multiple Trp-motifs on the precursor peptides have been discovered more frequently. These enzymes install C–C or C–O cross-links at the three-residue motifs between Trp-C5/C6/C7 and an sp3 carbon side chain to generate strained macrocycles. This mini-review will focus on the rSAM enzymes, WprB, OscB, XncB, FwwB and RscB to summarize the biosynthesis and NMR characterization of Trp-containing cyclophane products, and promiscuity of these enzymes.